SYSTEMATIC LITERATUR REVIEW (2021-2025): PENGEMBANGAN E-BOOK INTERAKTIF DALAM PEMBELAJARAN IPA DI SEKOLAH DASAR - Ricky, Aira Septia; Umamah, Fadhillatul; Amalia, Sofitri Nur; Trisnawati, Eka (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2025)
The advancement of digital technology has driven a transformation in educational technology, including in elementary science (IPA) learning, which requires the understanding of abstract concepts. This article aims to analyze five scientific publications from 2021 to 2025 that discuss the development and utilization of interactive e-books in science learning at the elementary school level. The review was conducted using the Systematic Literature Review (SLR) method with the PRISMA approach. The findings indicate that interactive e-books are valid, practical, and effective in enhancing students’ interest, engagement, and learning outcomes. The developed media generally utilize the Canva platform and integrate text, images, videos, animations, and interactive activities that align with students’ learning styles. Pedagogical approaches such as SAVI (somatic, auditory, visual, and intellectual) further strengthen the effectiveness of the media. All reviewed articles adopted the ADDIE or 4D development model, demonstrating high media validation scores and significant improvements in both affective and cognitive aspects of students. This study is limited by the small number of reviewed articles and the lack of diversity in digital platforms. Further research is recommended to include a broader range of articles and digital tools. ABSTRAKPerkembangan teknologi digital mendorong transformasi dalam media pembelajaran di sekolah dasar, khususnya pada pembelajaran Ilmu Pengetahuan Alam (IPA) yang menuntut pemahaman konsep abstrak. Literatur review ini bertujuan untuk menganalisis hasil-hasil penelitian terbaru (2021–2025) mengenai pengembangan dan pemanfaatan e-book interaktif dalam pembelajaran IPA pada siswa sekolah dasar. Kajian dilakukan menggunakan metode Systematic Literature Review (SLR) dengan pendekatan PRISMA dan menghasilkan lima artikel terpilih yang relevan. Hasil kajian menunjukkan bahwa e-book interaktif terbukti valid, praktis, dan efektif dalam meningkatkan minat, keterlibatan, serta hasil belajar siswa. E-book yang dikembangkan umumnya memanfaatkan platform Canva, mengintegrasikan teks, gambar, video, animasi, dan aktivitas interaktif yang sesuai dengan gaya belajar siswa. Selain itu, pendekatan pedagogis seperti SAVI (Somatis, Auditori, Visual, dan Intelektual) juga  memperkuat efektivitas media. Seluruh artikel yang direview menggunakan model pengembangan ADDIE atau 4D,  dengan hasil validasi media yang tinggi serta peningkatan signifikan dalam aspek afektif dan kognitif siswa. Keterbatasan kajian ini terletak pada jumlah artikel yang terbatas dan kurangnya variasi platform digital yang dikaji. Kajian ini merekomendasikan penelitian lebih lanjut dengan cakupan artikel dan platform yang lebih luas.